2006
DOI: 10.1203/01.pdr.0000242340.45676.5d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetic Polymorphisms on Bone Disease of Preterm Infants

Abstract: Bone disease is an important complication among very low birth weight (VLBW, Ͻ1500 g) infants. In adults, osteoporosis is associated with polymorphisms of vitamin D receptor (VDR), estrogen receptor (ER), and collagen I␣1 (COLIA1) genes. However, limited information is available regarding the role of these polymorphisms in bone disease in premature infants. We have investigated the possible association between bone disease and the allelic polymorphisms of these three genes in 65 VLBW infants. Twenty infants (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…However, clinical trials have shown that vitamin D supplementation of pregnant women reduces the risk for preeclampsia and gestational diabetes which represent risk factors for MBD (11, 12). Male gender and polymorphisms of vitamin D receptor, estrogen receptor, and collagen alpha 1 genes have also been indicated as risk factors for MBD in preterm infants (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical trials have shown that vitamin D supplementation of pregnant women reduces the risk for preeclampsia and gestational diabetes which represent risk factors for MBD (11, 12). Male gender and polymorphisms of vitamin D receptor, estrogen receptor, and collagen alpha 1 genes have also been indicated as risk factors for MBD in preterm infants (13).…”
Section: Introductionmentioning
confidence: 99%
“…Male sex, breastfeeding, and sepsis increase the risk of severe MBD. Compared with female infants, male infants have a low renal tubular reabsorption rate and increased renal phosphorus excretion, which may be related to delayed kidney maturity, leading to the occurrence of hypophosphatemia, which is a risk factor for MBD in preterm infants (19,20). Compared with preterm infant formula or intensive breastfeeding, breastfed preterm infants have lower phosphate levels (21); Adamkin et al (22) have shown that the prevalence of rickets in breastfed preterm infants is 40%, and formula milk powder has reduced the prevalence to 16%; this may be due to that intensive breastfeeding or formula milk feeding provides adequate calcium and phosphorus for premature infants and helps prevent MBD.…”
Section: Discussionmentioning
confidence: 99%
“…Early MBD is associated with male sex, increased initial ALP levels, and breastfeeding. Human milk alone may have inadequate protein and mineral content to promote optimal growth in the preterm infant because phosphate levels are lower in premature babies and breastfed infants (19)(20)(21). A lower phosphate level accompanied by initial high ALP levels and the effect of accumulation over time would affect bone mineralization, leading to the early occurrence of MBD.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for MBD in preterm infants are male gender and polymorphisms of certain genes (vitamin D receptor, oestrogen receptor, and collagen alpha 1 genes) [ 33 ].…”
Section: The Role Of Epigenetics In the Regulation Of Placenta And Fo...mentioning
confidence: 99%